UPAYA MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR MATEMATIKA MELALUI PROBLEM SOLVING SISWA KELAS VII SMP N 1 BOTODAYAAN RONGKOP GUNUNGKIDUL - Fitriana Rahmawati; Agustina Sri Purnami (Universitas Sarjanawiyata Tamansiswa, 2014)
The purpose of this research is to improve the activity and mathematics achievement of students of class VII with learning methods of problem solving in SMP N 1 Botodayaan, Rongkop, Gunungkidul. This research is Classroom Action Research (CAR). Techniques of data collection in this study was done by observation, documentation, and testing. Test instrument used to test the test item, whereas the observation sheet used to determine the level of involvement of the student. Data analysis techniques for observation sheet was conducted to determine student activity, whereas for mathematics achievement tests done by calculating the average value of the class. The results showed that after the application of the learning methods of problem solving, activity and learning mathematics achievement increased. It can be shown an increase in the average yield percentage of student activity sheets based on the observation that pre-cycle by 37.88% student activity, student activity first cycle of 51.01%, 76.77% for the second cycle. While the average value of student mathematics achievement increased from an average initial value of 56.97 to 66.16 in the first cycle and second cycle being 71.59. It is expected that schools can apply the learning method.